Relapse with isolated peritoneal metastasis in lung adenocarcinoma: case report and review of the literature - Tanriverdi, Ozgur; Barutca, Sabri; Meydan, Nezih (Contemporary Oncology/Współczesna Onkologia, 2012)
Lung cancer rarely involves the peritoneum without involvement of other metastatic sites. The most common regions of metastasis are the pleura, lung parenchyma, skeletal system, liver, brain, and adrenal glands. Compared with pleural metastasis, peritoneal involvement is rarely encountered in lung carcinoma. Ascites development is often described during late stages of the disease, following diagnosis in patients with serosal involvement other than pleural metastases. Diagnosis is based on histopathological or cytological examination confirmed by the presence of malign cells in the peritoneal fluids. Metastatic involvement of other areas is common and expected in cancer patients in whom peritoneal metastasis develop. There are no pulished reports of lung cancer cases with involvement of only the peritoneum without metastases to other more common regions. Herein we present a rare case of non-small cell lung carcinoma involving the peritoneum. The presented case had an unusual course and relapsed with peritoneal carcinomatosis without involvement of other regions.